Efficacy evaluation of a supplemental polyherbal immunopotentiator liquid on broiler chicken health - Gopal, Bhagwat Vishwanath; Krishnappa, Varun Kumar (International Journal of Veterinary Sciences Research, 2024)
A chicken’s immune system is crucial for its health and disease resistance, as it directly impacts production performance. Immunomodulators are substances such as vitamins, adjuvants, polysaccharides, probiotics, prebiotics, and botanicals that help regulate the immune system and enhance disease resistance. A study was conducted with Cobb 430Y broilers to evaluate the effect of a liquid multi-herb preparation "Immunopotentiator liquid (IPL)" on immunity, performance, and carcass characteristics. The study involved 126 chickens, randomly divided into six groups of 21 birds: G1, G2, G3, G4, G5 and G6. The G3 and G5 groups were supplemented with Geriforte Vet Liquid (GVL), while the G4 and G6 groups were supplemented with IPL. GVL and IPL supplemented by mixing with daily drinking water at 5 ml/100 birds at 1–2 weeks; 10 ml/100 birds at 2–4 weeks; and 20 ml/100 birds from four weeks onward till the chicks reached the marketable age, i.e., 38 days. Additionally, groups (G2, G5, and G6 groups) were vaccinated against New Castle Disease and Infectious Bursal Disease. The results showed that IPL supplementation improved growth performance parameters like body weight and feed efficiency without affecting carcass characteristics or serum biochemical parameters. Further, the immunity parameters, including ND and IBD titers, were elevated in chicks that received IPL supplementation along with vaccinations. In conclusion, the study showed that supplementing IPL with routine vaccinations for 21 days had a positive effect on the immunity, growth performance, and general health of Cobb 430Y broilers.